Cancer cell genotype associated tumor immune microenvironment exhibits differential response to therapeutic STING pathway activation in high-grade serous ovarian cancer. Issue 4 (4th April 2023) - Shakfa, Noor; Li, Deyang; Conseil, Gwenaelle; Lightbody, Elizabeth D; Wilson-Sanchez, Juliette; Hamade, Ali; Chenard, Stephen; Jawa, Natasha A.; Laight, Brian J.; Afriyie-Asante, Afrakoma; Tyryshkin, Kathrin; Koebel, Martin; et al.
Abstract : Background: High-grade serous ovarian carcinoma (HGSC) is the most lethal gynecologic malignancy characterized by resistance to chemotherapy and high rates of recurrence. HGSC tumors display a high prevalence of tumor suppressor gene loss. Given the type 1 interferon regulatory function of BRCA1 and PTEN genes and their associated contrasting T-cell infiltrated and non-infiltrated tumor immune microenvironment (TIME) states, respectively, in this study we investigated the potential of stimulator of interferon genes (STING) pathway activation in improving overall survival via enhancing chemotherapy response, specifically in tumors with PTEN deficiency. Methods: Expression of PTEN protein was evaluated in tissue microarrays generated using pretreatment tumors collected from a cohort of 110 patients with HGSC. Multiplex immunofluorescence staining was performed to determine spatial profiles and density of selected lymphoid and myeloid cells. In vivo studies using the syngeneic murine HGSC cell lines, ID8- Trp53 –/– ; Pten –/– and ID8- Trp53 –/– ; Brca1 –/–, were conducted to characterize the TIME and response to carboplatin chemotherapy in combination with exogenous STING activation therapy. Results: Patient tumors with absence of PTEN protein exhibited a significantly decreased disease specific survival and intraepithelial CD68+ macrophage infiltration as compared with intact PTEN expression. In vivo studies demonstrated that Pten -deficient ovarian cancer cells establish an immunosuppressed TIME characterized by increased proportions of M2-like macrophages, GR1+MDSCs in the ascites, and reduced effector CD8+ cytotoxic T-cell function compared with Brca1 -deficient cells; further, tumors from mice injected with Pten -deficient ID8 cells exhibited an aggressive behavior due to suppressive macrophage dominance in the malignant ascites. In combination with chemotherapy, exogenous STING activation resulted in longer overall survival in mice injected with Pten -deficient ID8 cells, reprogrammed intraperitoneal M2-like macrophages derived from Pten -deficient ascites to M1-like phenotype and rescued CD8+ cytotoxic T-cell activation. Conclusions: This study reveals the importance of considering the influence of cancer cell intrinsic genetic alterations on the TIME for therapeutic selection. We establish the rationale for the optimal incorporation of interferon activating therapies as a novel combination strategy in PTEN-deficient HGSC.